The Effects of Melatonin on the Physical Properties of Bones and Egg Shells in the Laying Hen - Taylor, Alexander C. (Public Library of Science, 2013)
Laying hens often experience unbalanced calcium utilization which can cause deficiencies in bone and egg mineralization. Because melatonin has been shown to affect bone mineralization in other animals, we examined whether treating hens with melatonin would affect eggshell thickness and improve skeletal performance, thereby reducing skeletal and egg shell defects. Birds were given a diet containing either low (30 µg/kg), medium (300 µg/kg), or high (3 mg/kg) concentrations of melatonin, or control feed through approximately one laying cycle. We examined the weight, length, and strength of egg, femur, tibia, and keel. Hens treated with a high concentration of melatonin showed significant strengthening in their femur and tibia, as measured by maximum force sustained and breaking force, compared to controls. Egg weights from hens treated with melatonin were significantly greater than those from hens that were not treated with melatonin. Conversely, egg shell mass of hens treated with melatonin was significantly lower than those of hens not treated with melatonin. Our data suggest that melatonin may affect the allocation of calcium to bone at the expense of egg shell mineralization.